2019
DOI: 10.1158/1078-0432.ccr-18-2392
|View full text |Cite
|
Sign up to set email alerts
|

Functional Silencing of HSD17B2 in Prostate Cancer Promotes Disease Progression

Abstract: Our findings provide evidence of the clinical relevance, significance and regulation of HSD17B2 in prostate cancer progression, which might provide new strategies for clinical management by targeting the functional silencing mechanisms of HSD17B2.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Although mCRPC is more likely to occur following ADT, the majority of prostatic adenocarcinomas remain reliant on ARS. Such mechanisms comprise: (1) steroidogenesis upregulation within the prostate tumor, allowing the synthesis of endogenous androgens [ 20 , 73 , 74 ]; (2) higher AR expression in prostate tumor cells, mainly due to AR gene amplification [ 22 ]; (3) single point mutations within AR gene LBD [ 75 , 76 , 77 ]; (4) silencing through methylation of the gene encoding the androgen-inactivation enzyme HSD17B2 [ 78 ]; (5) variants of the HSD3B1 gene [ 79 ]; (6) upregulation of the glucocorticoid receptor [ 80 ], and (7) emergence of AR splice variants.…”
Section: From Alterations To Ar Axis-targeted Therapy Resistancementioning
confidence: 99%
“…Although mCRPC is more likely to occur following ADT, the majority of prostatic adenocarcinomas remain reliant on ARS. Such mechanisms comprise: (1) steroidogenesis upregulation within the prostate tumor, allowing the synthesis of endogenous androgens [ 20 , 73 , 74 ]; (2) higher AR expression in prostate tumor cells, mainly due to AR gene amplification [ 22 ]; (3) single point mutations within AR gene LBD [ 75 , 76 , 77 ]; (4) silencing through methylation of the gene encoding the androgen-inactivation enzyme HSD17B2 [ 78 ]; (5) variants of the HSD3B1 gene [ 79 ]; (6) upregulation of the glucocorticoid receptor [ 80 ], and (7) emergence of AR splice variants.…”
Section: From Alterations To Ar Axis-targeted Therapy Resistancementioning
confidence: 99%
“…AKR1C3 , type 5 17β-hydroxysteroid dehydrogenase; HSD11B2, type 2 11β-hydroxysteroid dehydrogenase; and SRD5A1/2 , type 1 and type 2 steroid 5α-reductase (3a-hydroxysteroid oxidase) work as the molecular switch that determines DHT ligand access to the AR in the normal and diseased prostate [53] . HSD17B2 and HSD17B4 by working as 17β-hydroxysteroid oxidases convert T and DHT to their inactive counterparts, e.g., Δ 4 -AD and 5α-androstane-3,17-dione, respectively, and are implicated in the inactivation of these hormones [54,55] . The 5α-androstanediols once formed by AKR1C1 and AKR1C2, can then be glucuronidated by UGT family members UGT2B15 and UGT2B17 [56,57] .…”
Section: Intracrine Androgen Biosynthesismentioning
confidence: 99%
“…More so, ~54.3% of patients with metastatic AR positive tumors concurrently expressed enzymes for adrenal androgen utilization, such as SRD5A1 and SHBG, and 25.7% expressed enzymes for de novo steroidogenesis, including hydroxysteroid 17-β-dehydrogenase 2 and 3 (HSD17B2/3) [ 8 ]. It has been suggested that HSD17B2 suppresses androgen production by reverse conversion of testosterone or DHT to their upstream precursors, that the expression of HSD17B2 reduces as PCa progresses, and that the overexpression of HSD17B2 suppresses androgen-induced cell proliferation and xenograft growth [ 9 ].…”
Section: Introductionmentioning
confidence: 99%